2007
DOI: 10.1007/s00018-007-7499-7
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxicity of eosinophil cationic protein/ribonuclease 3 on eukaryotic cell lines takes place through its aggregation on the cell membrane

Abstract: Human eosinophil cationic protein (ECP)/ ribonuclease 3 (RNase 3) is a protein secreted from the secondary granules of activated eosinophils. Specific properties of ECP contribute to its cytotoxic activities associated with defense mechanisms. In this work the ECP cytotoxic activity on eukaryotic cell lines is analyzed. The ECP effects begin with its binding and aggregation to the cell surface, altering the cell membrane permeability and modifying the cell ionic equilibrium. No internalization of the protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 43 publications
1
65
1
6
Order By: Relevance
“…This eosinophil protein has been described for its tumoricidal effect (46)(47)(48)(49) and pore membrane-forming properties (50,51). A recent study showed that ECP was not internalized (52). Membrane immunofluorescence pathway of ECP released during coculture was consistent with a pore-forming effect.…”
Section: Discussionmentioning
confidence: 83%
“…This eosinophil protein has been described for its tumoricidal effect (46)(47)(48)(49) and pore membrane-forming properties (50,51). A recent study showed that ECP was not internalized (52). Membrane immunofluorescence pathway of ECP released during coculture was consistent with a pore-forming effect.…”
Section: Discussionmentioning
confidence: 83%
“…ECP has been found to attach to cell membrane altering permeability as well as increasing production of reactive oxygen species [Navarro et al 2008]. MBP was also found to cause alveolar epithelium cell lysis allowing for penetration of inhaled antigen [Ayars et al 1985].…”
Section: Introductionmentioning
confidence: 99%
“…The infiltrating eosinophils release several toxic and proinflammatory mediators which induce epithelial injury, airway hyper-responsiveness, and airway remodeling [6][7][8]. Therefore, eosinophils are regarded as potential therapeutic targets in allergic diseases and asthma [9].…”
Section: Introductionmentioning
confidence: 99%